36.2k views
22 votes
What is the solution to the system of equations below?

(Hint: Sole using substitution)
y=2x+1
3x + y=-9
The solution is

User Solkar
by
4.2k points

1 Answer

10 votes

y=2x+1
3x + y=-9


3x + y=-9 is the same as y=-3x-9

y=2x+1
y=-3x-9

2x+1 = -3x-9

—-add 3x on both sides

5x+1=-9

—-subtract 1 from both sides

5x=-10

—-divide 5 on both sides

5x/5 = -10/5

x = -2

——now plug in x in one of the equations to find y

y=2x+1

y=2(-2)+1

y=-4+1

y=-3


The solution is (-2,-3).
User SimpleSpawn
by
4.6k points